(untitled) (Revista de Ciências Agroveterinárias, 2015)
With advances of farming and research in the area of molecular genetics, studies that can help with obtaining good quality DNA are necessary. The objective was to evaluate the efficiency of DNA extraction in different types of tissues of three species of carp by using the protocol of DNA extraction with Sodium Chloride (NaCl). The samples were subjected to DNA extraction, and the integrity was visualized on 1.5% agarose gel. In a total of 72 samples used for DNA extraction, all of them were positive, confirmed by the presence of bands on agarose gel. The capacity of amplifying the extracted DNA was tested by amplification reactions using the RAPD (random amplification of polymorphic DNA) technique, confirming that the DNA was of good quality for use in subsequent studies with molecular markers.